Impact of bus electrification on carbon emissions: The case of Stockholm. (1st February 2019) - Xylia, Maria; Leduc, Sylvain; Laurent, Achille-B.; Patrizio, Piera; van der Meer, Yvonne; Kraxner, Florian; Silveira, Semida
Abstract: This paper focuses on the potential impact of various options for decarbonization of public bus transport in Stockholm, with particular attention to electrification. An optimization model is used to locate electric bus chargers and to estimate the associated carbon emissions, using a life cycle perspective and various implementation scenarios. Emissions associated with fuels and batteries of electric powertrains are considered to be the two main factors affecting carbon emissions. The results show that, although higher battery capacities could help electrify more routes of the city's bus network, this does not necessarily lead to a reduction of the total emissions. The results show the lowest life cycle emissions occurring when electric buses use batteries with a capacity of 120 kWh. The fuel choices significantly influence the environmental impact of a bus network. For example, the use of electricity is a better choice than first generation biofuels from a carbon emission perspective. However, the use of second-generation biofuels, such as Hydrotreated Vegetable Oil (HVO), can directly compete with the Nordic electricity mix. Among all fuel options, certified renewable electricity has the lowest impact. The analysis also shows that electrification could be beneficial for reduction of local pollutants in the Stockholm inner city; however, the local emissions of public transport are much lower than emissions from private transport. Highlights: Larger batteries support electrification of more routes, but emissions do not necessarily decrease. Heavier batteries lead to increased energy consumption and fuel-associated emissions. Second generation biofuels compete with the Nordic electricity mix in terms of emission reduction.